Significant effects of online news on vote choice: a review - Alivi, Mumtaz Aini; Ahmad Ghazali, Akmar Hayati; Tamam, Ezhar (Inderscience Enterprises, 2018)
Current trend around the world witnesses the usage of online news widely to spread news to reach certain audiences. It was also chosen by the public in recent years as a source to obtain news compared to the traditional media due to degree of freedom offered by the medium. This review paper examines four main issues related to the key predictor for vote choice: information highlighted in online news, satisfaction with the government, candidate personality and political party performances. Studies revealed that online news has a significant effect towards vote choice. News highlighted on online channels has the capacity to change the people's perception about a country's political rule and development. It will ultimately be translated into vote choices, namely in deciding the best candidate or political party which the public believes can serve them in forming a better nation.